KAJIAN METODE KRITIK MATAN HADIS - Sofyan, Idha Fadhilah; Wiwik Permatasari; Muhammad Amin Sahib; Abd. Rahman Sakka (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2023)
As Muslims we cannot be separated from references to the rules of the Qur’an and hadis in our daily lives. Where the Al Qur’an is the source of transmission that takes place mutawatir, while some of the Hadis narrations take place mutawatir and some take place on ahad basis. From this, various issues of criticism of sanad and matan Hadis arise in various circles of Hadis researchers. Some researchers argue that criticism of Hadis has so far mostly discussed the issue of sanad criticism, but only a few have discussed the issue of matan criticism. Meanwhile from the matan perspective, this Hadis research will actually strengthen the quality of the Hadis sanad. In a Hadis it is necessary to have a critique of sanad and matan in order to find out which type of Hadis is makbul or mardud. For this reason, the purpose of this study is to examine in depth the criticism of Matan Hadis using several existing methods. The research method used is a qualitative method with data collection techniques based on library research which is a data collection system by finding sources such as books, journals, and other scientific papers. This research also uses content analysis, which is reasearch that aims to analyze the content, understand, and know about criticism of the Hadis matan. The results of the study show that there is a method used in criticizing the hadis matan and there are also minor and major rules used in the process of criticizing the Hadis matan, as well as examples of critique of hadis matan at the time of companions. For this reason, Muslims from various circles can understand the study of the critique of Matan Hadis in this study.